SIMILAR BUT NOT THE SAME: HOW TO IDENTIFY THE NAME OF ARAB DESCENDANT AND THE ARABIC NAME OF JAVANESE - Aribowo, Eric Kunto; Hadi, Syamsul; Ma'ruf, Amir (Arabi : Journal of Arabic Studies, 2019)
Arabic names are not only used by Arab (descendants) but also by most Muslims in the world, including in Indonesia. This phenomenon will certainly be difficult when one wants to distinguish Arab (descendants) from non-Arabs who adopt Arabic or Islamic names. This study aimed to identify and explore the linguistic characteristics of the names of Arab descendants in Indonesia that distinguish them from the names of Muslim Javanese. By using population data samples in Pasar Kliwon Subdistrict taken from SIAK by Population and Civil Registration Agency Surakarta as of February 28, 2018, as many as 84,126 names were sorted and classified between Arab descendants and Muslim Javanese names using the onomastics framework. The results showed that the names of Arab descendants tended to use Arabic with the influence of the Yemeni dialect. The adoption of the name of the father and paternal grandfather also became another characteristic besides the presence of surname at the end of the proper name.